Camera in times of crisis : focus on Africa - Adewumi, Kehinde Christopher; Olalere, Folasayo Enoch; Duniya, Gambo Giles (Emerald Publishing Limited, 2025)
Volume 37 of Advances in Management Accounting uses a variety of methods, from experiments and case studies to surveys, to build upon existing knowledge within the management accounting discipline. Containing a diverse range of authors from around the world, this publication focuses on theoretically sound and practical research which has a cutting-edge and wide-reaching appeal to academics and practitioners. Showcasing methods of and analysis on varied statistical testing and performance measurement models, this edited collection will appeal to both management accounting academics and professionals. Topics analysed include the effects and significance of statistical testing, the limits and goals of such testing and modelling, compensation moderation, and how to handle ethical issues affecting management accounting. Advances in Management Accounting (AIMA) publishes thought-provoking volumes that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. The series seeks thoughtful, well-developed articles on a variety of current topics in management accounting, broadly defined. AIMA seeks to publish commentaries on research methodology and new management accounting areas of interest as well as papers using research methods including survey research, field tests, case studies, experiments, meta-analyses, and modelling.
Includes index.
Keywords: Sociology -- Africa.; Social Science -- Cultural & Ethnic Studies -- African Studies.; Sociology.; Ethnic studies.; Africa.; elektronické knihy; electronic books